Marianne Hirsch and Leo Spitzer, School Photos in Liquid Time: Reframing Difference (Seattle: University of Washington Press, 2020), 264 pp, ISBN 978-0295746548 - du Plessis, Rory (Kronos: Southern African Histories, 2021)
In the path-breaking book School Photos in Liquid Time, Marianne Hirsch and Leo Spitzer provide a novel study of school photographs. Unlike family photo albums and archived photographic records, school photographs have received minimal scholarly interest (p. 26). To this end, the book is commended for offering a full-length study devoted to school photos and for directing academic attention to a genre of vernacular photography that has received only a paucity of scholarly and historical investigation. The book offers a sustained focus on school photos taken in ‘times of extremity’ (p. 16), for example, of Jewish children in Nazi ghettos, and black children during the colonial period of the late nineteenth and early twentieth centuries. Significantly, for this group of school photos, Hirsch and Spitzer develop a ‘“liquid” and multitemporal reading’ (p. 13) that seeks to underscore how the meaning of photographs can develop ‘in unforeseen directions when they are viewed and re-viewed by different people in different presents. In “liquid time” they are not fixed into static permanence; rather, they remain dynamic, unfixed, as they acquire new meanings, in new circumstances’ (p. 13).